Etimologija Hieronimovega imena - Božič, Anja (Tretji dan (Ljubljana), 2024)
The article deals with various etymological interpretations of the name Hieronymus in medieval and early modern hagiographical texts. First it looks into the false interpretations in his earliest biographies, e.g. in Plerosque nimirum and in Golden Legend. Then it focuses on the interpretation of Pier Paolo Vergerio the Elder, who first gave the correct explanation of the name Hieronymus, owing to his knowledge of Greek. Finally the article brings some examples of scribal mistakes in the writing of the Greek words from which Jerome’s name is composed.
Keywords: etimologija; etimology; Greek; grščina; hagiografije; Hieronymus; Jerome; manuscripts; rokopisi; svetniki; Vergerio, Pietro Paolo